Mortalidad neonatal en el Estado Plurinacional de Bolivia: Desigualdades territoriales en el acceso a los servicios de salud - Inés Valeria Lagrava León (Institute for Advanced Development Studies (INESAD), 2018)
– Despite the efforts made to reduce neonatal mortality in the Plurinational State of Bolivia, and the implementation of the Universal Maternal and Child Health Insurance (SUMI), the data reveal that progress has been slower than achieved in terms of reducing infant mortality in general. In this context, the main interest of this research is to define the characteristics of neonatal mortality in the country. The study starts with the econometric analysis of data from the 2008 National Demographic and Health Survey (ENDSA). The objective is to visualize how the place of origin affects the risk of death of the newborn. The findings reveal that, in the Plurinational State of Bolivia, the risk of neonatal death is conditioned by access to health services, due to territorial disparities at the urban and rural levels. These disparities translate into economic, geographic and exclusion barriers. Those barriers diminish equity in the access and use of health services. In addition, they reinforce the social determinants affecting the death of the newborn and limiting access to timely interventions and adequate in maternal-neonatal care.
Keywords: I15; I14; J18; C25; O54; 330; neonatal mortality; access to health services; urban; rural; Bolivia